2022
DOI: 10.3389/fmed.2022.893306
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Complex Treatment Using Vibroacoustic Therapy in a Patient With Co-Infection and COVID-19

Abstract: The present report highlights a case of successful treatment of a 59-year-old patient who experienced pain, swelling, hyperemia, the presence of a wound of the right knee joint, impaired function of the right lower limb, weakness, fatigue, and labored breathing. Sepsis was detected in the patient as a result of periprosthetic infection with concomitant severe COVID-19. The patient was admitted to the hospital for 59 days, with 57 days of treatment of the patient at the intensive care unit. A therapy of multipl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 19 publications
0
3
0
3
Order By: Relevance
“…Results. Against the background of complex therapy in combination with the course of VALT, patients in the study group showed a statistically significant decrease in the duration of hospitalization to 19 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) days, as opposed to 27 (24-34) days (p = 0.003) in the control group. When comparing the changes in the indicators of the surviving patients of the study group, a positive dynamics of the main indicators against the background of VALT was obtained: ∆VAS -2 (-3; -1), р = 0.000; ∆SpO2-6 (2; 7), р = 0.002; ∆PaO2-13 (2; 19), р= 0.001 in comparison with the dynamics of similar indicators of the control group.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Results. Against the background of complex therapy in combination with the course of VALT, patients in the study group showed a statistically significant decrease in the duration of hospitalization to 19 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) days, as opposed to 27 (24-34) days (p = 0.003) in the control group. When comparing the changes in the indicators of the surviving patients of the study group, a positive dynamics of the main indicators against the background of VALT was obtained: ∆VAS -2 (-3; -1), р = 0.000; ∆SpO2-6 (2; 7), р = 0.002; ∆PaO2-13 (2; 19), р= 0.001 in comparison with the dynamics of similar indicators of the control group.…”
Section: Introductionmentioning
confidence: 95%
“…Сравнение длительности госпитализации исследуемой группы и группы контроля показывает статистически значимое уменьшение показателя на фоне применения ВАЛТ (в исследуемой группе -19 (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29) дней, в группе контроля -27 (24-34) дней (p = 0,003)).…”
Section: результатыunclassified
See 2 more Smart Citations
“…Sound-distributed stimulation to the endothelial cell matrix can trigger mechanosensors in cells affected by PSS and has been shown to increase eNO, can induce the expression of the mechanosensory protein Syndecan-4 (Syn4) and VEGF, as well as increase blood flow and clot dissolution [ 196 , 197 , 198 , 199 , 200 ]. This method may also be a plausible therapeutic strategy for MI [ 201 , 202 ] and sepsis [ 203 ].…”
Section: Limitationsmentioning
confidence: 99%